Telling stories of race: a study of racialised subjectivity in the post-apartheid academy - Kiguwa, Peace (My University, 2015)
This study draws on in-depth interviews conducted with twenty black students from different socioeconomic and cultural backgrounds studying at the University of the Witwatersrand in Johannesburg, South Africa at both undergraduate and postgraduate levels. It attempts to explore and understand some of the complexities of racial subjectivities in a post-apartheid and racially diverse institutional context through Bourdieu’s constructs of habitus and field. Furthermore the psychosocial and phenomenological approach to theorizing black subjectivity evident in the theories of Fanon and Du Bois are further used to explore the complexities of racialised habitus. Bourdieu argues that encounter with an unfamiliar field will result in transformed habitus (socialized subjectivity). The subject’s movement and participation in different and unfamiliar fields will result in habitus that is conflicted and fraught with tension. Through a critical heremeneutic approach the analyses suggests much more complex, ambiguous and contradictory articulations of racialised subjectivity that manifest in relation with dimensions of cultural capital. These in turn produce complex processes of racialization for these students. The narrative analysis of content explores thematic content of the data and demonstrates dominant themes related to constructs of racialised subjectivity, with particular focus on ‘blackness’ as a distinct and contradictory construct. Through positive and negative constructs of blackness, both interpersonal and generalized interaction patterns of these students on campus is shown to reflect intricate ways that racialised boundaries are both created and sustained. The discursive layer of analysis further demonstrates the at times essentializing and contradictory deployment of race used by the students in their navigation of the academic field. The analysis of form further highlights similar and diverse academic trajectories of the students that are interwoven with accounts of racialised and classed histories. These accounts highlight the perceived importance of race in the accruement of cultural capital attributes both prior to and during their immersion within the academic context at tertiary level. The study argues for a more concerted effort at documenting the lived experiences of racialization including the subjective negotiation of multiple and contradicting interpellation processes within higher education more generally. Key Words: race, subjectivity, habitus, field, students, tertiary institution, Bourdieu, Fanon, Du Bois
This report is submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in the Faculty of Humanities at the University of the Witwatersrand. Johannesburg, February 2014